Implementasi Konsep Blue Economy di Indonesia sebagai Upaya Mewujudkan Sutainable Development Goals (SDgs) 14: Life Below Water - Aprilia; Mulyanie, Erni (Jurnal Ilmiah Samudra Akuatika, 2023)
in the marine living sector, specifically in the capture and aquaculture sector, Indonesia is still experiencing difficulties in meeting sustainability standards. The sustainability value of Indonesian fisheries in the Ocean Health Index (OHI) is ranked 175th out of 220 countries in the food provision indicator which calculates food security from maritime resources with the ability to balance ecology and exploitation. The decline in ecological balance, such as the carrying capacity of the sea, is caused by conservation that is less oriented towards sustainable management. This research aims to describe the application of the blue economy concept in Indonesia in an effort to realize Sustainable Development Goals (SDGs) 14: life below water. The method used in this research is the literature study research method using descriptive analysis techniques. One of the uses of marine resources in Indonesia is in the fisheries and mining sectors. Capture fisheries production in Indonesia has increased every year, based on data from the Ministry of Maritime Affairs and Fisheries in 2019, the total production of captured fish in 2017 was 6,424,114 tonnes, in 2018 it was 6,701,834 tonnes, and in 2019 it was 7,164,302 tonnes. Meanwhile, the energy and mineral resources sectors still make a major contribution to national development. The oil and gas subsector has made the largest contribution to the energy and mineral resources sector over the last three years, with an average contribution of 30% to GDP. Through the blue economy concept, it is a concept that ensures the preservation of marine resources and the coastal environment and encourages the use of resources to improve the economy in the marine and fisheries industrial sector. The strategy for implementing the blue economy concept is certainly relevant to the Sustainable Development Goals (SDGs) point 14, namely life below water or marine ecosystems.